Innate signalling molecules as genetic adjuvants do not alter the efficacy of a DNA-based influenza A vaccine - Lapuente, Dennis; Stab, Viktoria; Storcksdieck, Michael; Maaske, Andre; Köster, Mario; Xiao, Han; Ehrhardt, Christina; Tenbusch, Matthias (PLoS ONE, 2020)
In respect to the heterogeneity among influenza A virus strains and the shortcomings of current vaccination programs, there is a huge interest in the development of alternative vaccines that provide a broader and more long-lasting protection. Gene-based approaches are considered as promising candidates for such flu vaccines. In our study, innate signalling molecules from the RIG-I and the NALP3 pathways were evaluated as genetic adjuvants in intramuscular DNA immunizations. Plasmids encoding a constitutive active form of RIG-I (cRIG-I), IPS-1, IL-1β, or IL-18 were co-administered with plasmids encoding the hemagglutinin and nucleoprotein derived from H1N1/Puerto Rico/8/1934 via electroporation in BALB/c mice. Immunogenicity was analysed in detail and efficacy was demonstrated in homologous and heterologous influenza challenge experiments. Although the biological activities of the adjuvants have been confirmed by in vitro reporter assays, their single or combined inclusion in the vaccine did not result in superior vaccine efficacy. With the exception of significantly increased levels of antigen-specific IgG1 after the co-administration of IL-1β, there were only minor alterations concerning the immunogenicity. Since DNA electroporation alone induced substantial inflammation at the injection site, as demonstrated in this study using Mx2-Luc reporter mice, it might override the adjuvants' contribution to the inflammatory microenvironment and thereby minimizes the influence on the immunogenicity. Taken together, the DNA immunization was protective against subsequent challenge infections but could not be further improved by the genetic adjuvants analysed in this study.
CRIS-Team Scopus Importer:2020-04-17